2017
DOI: 10.1152/jn.00836.2016
|View full text |Cite
|
Sign up to set email alerts
|

Descending antinociception induced by secondary somatosensory cortex stimulation in experimental neuropathy: role of the medullospinal serotonergic pathway

Abstract: Stimulation of the secondary somatosensory cortex (S2) has attenuated pain in humans and inflammatory nociception in animals. Here we studied S2 stimulation-induced antinociception and its underlying mechanisms in an experimental animal model of neuropathy induced by spinal nerve ligation (SNL). Effect of S2 stimulation on heat-evoked limb withdrawal latency was assessed in lightly anesthetized rats that were divided into three groups based on prior surgery and monofilament testing before induction of anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…The somatosensory cortex is also involved in descending anti-nociception through reducing "on" cell discharge in the rostral ventromedial medulla (RVM) in a 5-HT 1A receptor-dependent fashion [108]. Interestingly, the administration of lidocaine to the RVM of SNL rats relieved allodynia in animals exhibiting pain, but precipitated allodynia in rats that had also undergone surgery, but did not exhibit pain-related behaviors [109], consistent with the bi-directional influence of the RVM in descending modulation.…”
Section: Changes In Brain Regionsmentioning
confidence: 99%
“…The somatosensory cortex is also involved in descending anti-nociception through reducing "on" cell discharge in the rostral ventromedial medulla (RVM) in a 5-HT 1A receptor-dependent fashion [108]. Interestingly, the administration of lidocaine to the RVM of SNL rats relieved allodynia in animals exhibiting pain, but precipitated allodynia in rats that had also undergone surgery, but did not exhibit pain-related behaviors [109], consistent with the bi-directional influence of the RVM in descending modulation.…”
Section: Changes In Brain Regionsmentioning
confidence: 99%
“…The role of the 5-HT 1 receptor family except 5-HT 1E in pain has been long studied both together and separately. Among them, the 5-HT 1A receptor has been extensively investigated for its analgesic effect in multiple pain states, including neuropathic, inflammatory, and visceral pain [61][62][63]. The activation of the 5-HT 1A receptor inhibits adenylyl cyclase thus reducing the intracellular concentration of cyclic adenosine monophosphate (cAMP), and subsequently, K + channels open and Ca 2+ channels close, resulting in an inhibition of neuronal firing [64].…”
Section: The Role Of Serotonergic System In Descending Pain Modulationmentioning
confidence: 99%
“…Glutamate administration in the central amygdala (CeA) produced bidirectional effects: increased hypersensitivity that was reversed by a spinal 5-HT 3 receptor antagonist and decreased hypersensitivity that was blocked by a spinal 5-HT 1A receptor antagonist, indicating a CeA-spinal descending pathway in pain modulation [71]. Somatosensory cortex (S2) stimulation caused antinociception in a spinal nerve ligation (SNL) model, and this effect was prevented by chemically activating 5-HT 1A receptors in the RVM or blocking 5-HT 1A receptors spinally, illustrating that S2 stimulation-induced analgesia in neuropathic pain is mediated by medullospinal descending serotonergic pathways [63]. In visceral pain, a clinical trial showed that tandospirone citrate (a partial agonist of 5-HT 1A receptors) had benefits in suppressing the abdominal symptoms of patients with functional dyspepsia [62], which was consistent with animal experiments [66].…”
Section: The Role Of Serotonergic System In Descending Pain Modulationmentioning
confidence: 99%
“…Together, the amygdala-periaqueductal grey-raphé axis can provide context-dependent control of pain integrating multiple inputs from the periphery (including nociceptors) and from other brain regions, including the somatosensory cortex 2 (SS2; Bourbia & Pertovaara, 2018). Electrical stimulation of the somatosensory cortex 1 (SS1) in rats with developed mechanical hypersensitivity attenuated pain involving spinal 5-HT 1A receptors (Sagalajev et al, 2017). Thus, there are multiple centres in the brain at different levels starting from the cortex that activate 5-HTcontaining processes culminating at the level of the brainstem and spinal cord.…”
Section: Brainstem Raphé Nuclei As the Source Of Descending 5-ht Modulation Of Trigeminal Nociceptionmentioning
confidence: 99%